RANCANG BANGUN DC-DC CONVERTER TERKENDALI DALAM SISTEM PENGISIAN BATERAI PADA MODUL PEMBANGKIT LISTRIK TENAGA BAYU (PLTB) BERBASIS FUZZY - Hariyanti, Kiki Andes; Subito, Mery; Alamsyah, Alamsyah; Santoso, Rudi; Kali, Agustinus (Foristek, 2022)
The wind is one of the new renewable energy sources that can be used as a source of electrical energy. But the wind in nature has a speed that varies greatly with each time and place. This can be overcome by using the DC-DC Converter tool with a fuzzy method to produce a stable electrical voltage so that it becomes usable electrical energy. This tool uses a series of converters connected to the Arduino microcontroller. The DC-DC converter circuit in this study also uses a voltage sensor as feedback for the Fuzzy method to maintain the stability of the circuit output which varies from 2V-5V, so that it can maintain a voltage of 6.5V which is used as a 6V battery charging. This circuit has an average efficiency of 60% for the open-loop system and 63% for the closed-loop system.